The Role of Irisin , Insulin and Leptin in Maternal and Fetal Interaction - Okdemir, Deniz; Hatipoglu, Nihal; Kurtoglu, Selim; Siraz, Ulku Gui; Akar, Himmet Haluk; Muhtaroglu, Sabahattin; Kutuk, Mehmet Serdar (Galenos Yayincilik, 2018)
Objective: Insulin is an important hormone for intrauterine growth. Irisin is an effective myokine in the regulation of physiological insulin resistance in pregnancy. Leptin and insulin are associated with fetal growth and fetal adiposity. In this study, we aimed to investigate the relationships between irisin, insulin and leptin levels and maternal weight gain, as well as anthropometric measurements in the newborn. Methods: Eighty-four mothers and newborns were included in the study. Irisin, leptin and insulin levels were measured in the mothers and in cord blood. Anthropometric measurements in the newborn, maternal weight at the beginning of the pregnancy and at delivery were recorded. Results: Birth weight were classified as small for gestational age (SGA), appropriate for gestational age (AGA) and large for gestational age (LGA). There was no difference in irisin levels among the groups. Leptin and insulin levels were found to change significantly according to birth weight (p =0.013, and p =0.012, respectively). There was a negative correlation between the anthropometric measurements of the AGA newborns and irisin levels. This correlation was not observed in SGA and LGA babies. Leptin levels were associated with fetal adiposity. Conclusion: While irisin levels are not affected by weight gain during pregnancy nor by birth weight, they show a relationship with anthropometric measurements in AGA infants. These results may lead to the understanding of metabolic disorders that will occur in later life.
Keywords: Irisin; insulin; eptin; fetal growth; maternal weight gain